INFORMALITY IN THE ECONOMIC AND TAX EVASION OF TAXES IN PERU - Choy Zevallos, Elsa Esther (2011)
Peru is one of the Latin American countries that have higher rates of business informality which leads to a high degree of tax evasion. The activity in the informal economy that exists in our country is attributed, among its main causes, the cost of legality, legal restrictions and control activities established by law. The issue is important because it seeks to identify the relationship between the informal economy and tax evasion, which are listed, classified and reported issues related to national reality. Develop a framework of economic sectors, informality and tax evasion, discusses causes and consequences, and finally presents the conclusions and recommendations in order to improve tax collection in our country.